Covert and overt attention and the processing of cues for location and target identification. - Goolkasian, Paula; Tarantino, Mandy (Journal of General Psychology, 1999)
Part of a special issue on visual attention. Three experiments comparing covert and overt attention were conducted to test assumptions of space-based theories of visual attention. It was found that only when a target letter appeared consistently in the center a the display was there evidence for a traditional spotlight with a unitary focus of attention. In addition, it was found that when both overt and covert attention conditions included multiple target locations, the distractor competed for attention and lengthened reaction times in relation to its distance from and compatibility with the target. Such findings support an attentional mechanism that permits parallel access to noncontingent areas of the visual field.